THE EFFECT OF PROCESS ORIENTED GUIDED INQUIRY LEARNING MODEL BASED ON VIRTUAL LABORAORY TOWARD PROBLEM SOLVING ABILITIES OF PHYSICS STUDENT - Putu Wira Sanggara; Aris Doyan; Ni Nyoman Sri Putu verawati (Jurnal Penelitian Pendidikan IPA, 2019)
Abstract - This study aims to determine the effect of Process Oriented Guided Inquiry Learning model of Virtual Lab to the ability of solving physics problem of high school students of class X. This research type is quasi experiment with pretest-postest control group design research design. The population of this research is all students of class X MIPA SMAN 1 Kuripan with sampling technique using purposive sampling. There are two samples taken are the sample as experimental class given treatment in the form of learning using learning model POGIL assisted Virtual Lab and control class treated using conventional learning model. Data collection of problem-solving abilities is done by a blueprint test technique. The research hypothesis was tested by using the t-test polled variance with 5% significance. It was concluded that the use of Process Oriented Guided Inquiry Learning model (POGIL) with Virtual Lab has an effect on students problem solving ability with ttable = 2,00 <tcount = 3,11. Keywords: POGIL, Lab Virtual, Problem Solving Ability,